Kajian Metode Economic Order Quantity dan Reorder Point pada Aplikasi Point Of Sale - Raffa Ismunandar; Ade Andri Hendriadi; Garno Garno (Politeknik Harapan Bersama, 2018)
Inventory control can be said to increase the speed of work to achieve the level of energy efficiency and time in data management. Sales that have the transaction data still handwritten resulted in long enough time in recording the data, as well as the absence of determination of inventory and determining when the ordering of goods returned. Point of Sale Study with Economic Order Quantity (EOQ) and Reorder Point (RoP) Method will be used to overcome the problem, management of transaction data in which there are methods of calculating order quantity and reorder time can minimize operational cost and optimize inventory. The EOQ method is used as a stock inventory controller and the RoP method is used for warning notification to avoid negligence. Based on the result of the research, it can be concluded that Point of Sale Application with Economic Order Quantity and Reorder Point Method 90% accepted and able to overcome the problems that exist in Faranita Foam Store.